2015
DOI: 10.1177/1934578x1501000519
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Safranal as the Main Allelochemical from Saffron (Crocus sativus)

Abstract: Dried parts of 75 medicinal plant species collected from different regions in Iran were assayed by the Dish Pack Method for volatile allelopathic activity, using Lactuca sativa (lettuce) as the test plant. The highest (60%) inhibition was observed for saffron (stigma of Crocus sativus), followed by Dracocephalum kotschyi, Solanum nigrum and Artemisia aucheri. Safranal was identified as the main chemical by Headspace Gas Chromatography-Mass Spectrometry (HS-GC-MS) analyses of saffron. Moreover, the EC 50 of saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The cotton swab method, following GC-MS analysis was previously successfully applied for the determination of EC 50 of radicle and hypocotyl growth of lettuce seedlings by 1-decyne in the vapor phase and was found at the concentration of 0.5 ng/mL [29] and by safranal—1.2 µg/L (ppb) [30]. Additionally, previous results also demonstrated that octyl acetate, a major volatile from H. sosnowskyi fruits, had lower EC 50 for radicle and hypocotyl growth (64 and 57 ng/cm 3 , respectively), than the predominant octanal (EC 50 is 20 and 9 ng/cm 3 respectively), however, octanal was suggested to be the major contributor to its allelopathic activity based on total activity estimation [14].…”
Section: Resultsmentioning
confidence: 99%
“…The cotton swab method, following GC-MS analysis was previously successfully applied for the determination of EC 50 of radicle and hypocotyl growth of lettuce seedlings by 1-decyne in the vapor phase and was found at the concentration of 0.5 ng/mL [29] and by safranal—1.2 µg/L (ppb) [30]. Additionally, previous results also demonstrated that octyl acetate, a major volatile from H. sosnowskyi fruits, had lower EC 50 for radicle and hypocotyl growth (64 and 57 ng/cm 3 , respectively), than the predominant octanal (EC 50 is 20 and 9 ng/cm 3 respectively), however, octanal was suggested to be the major contributor to its allelopathic activity based on total activity estimation [14].…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to the high volatility and low solubility of the VOCs [12]. Some volatile bioactive compounds namely safranal and octanal identified in C. sativus and Heracleum sosnowskyi , respectively, were reported with strong inhibitory activity on plant growth and development [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to AMF, it would be advisable to investigate other endophytes to be co-inoculated with saffron bulbs, or directly recruited from soils, that could offer further advantages, for example, an increasing tolerance to biotic and/or abiotic stresses. This last aspect is of particular importance because, after a few years of continuous cultivation, saffron could exert allelopathic activity against many soil components [ 64 , 65 ], thus compromising both its replanting and the cultivation of alternative crops (i.e., lettuce) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%